A questão agrária na agenda governamental de FHC e Lula : uma análise à luz dos estudos de formação de agenda - Carvalho, Flávia Sanches de (2017)
This research has as general objective to analyze the trajectory and the movement of the agrarian question in the governmental agenda, from 1995 to 2006, based on the application of instruments that show the change in the priorities of this policy, specifically observing the Presidential Discourses, Decrees, Provisional Measures and Messages forwarded by the President of the Republic to the National Congress, based on a multidisciplinary view of public policies, notably the formation studies in the agenda-setting. The analysis used here, therefore, focuses on the process of changes in public policies focused on the governments FHC I and II and Lula I. So, that the objectives are achieved, this dissertation is based on the model of punctuated equilibrium (Punctuated Equilibrium Framework) Baumgartner and Jones (1993) which seeks, through temporal mapping of care indicators, analyze the rise and the changes of an issue on the government agenda over time. From the above model, will seek to clarify, explain and discuss the movement of land reform policies over twelve years of administrations. Thus, is expected to contribute to the studies in the field of public policies on the agenda of training in Brazil.